Tracheobronchial ossification in children: a case report and review of the literature - Ruan, Yan; Chen, Shan; Zhang, Ling; Huang, Huiyun; Tang, Weiwei; Li, Lizhi (Frontiers in Pediatrics, 2025)
ObjectiveThis study aimed to report a case of tracheobronchial ossification (TO) in a child and review the related literature on its clinical signs, diagnosis, differential diagnosis, pathological characteristics, points, and treatment measures.MethodsA retrospective analysis was conducted on the clinical data of one pediatric patient with TO admitted to the Department of Pediatrics, Fuzhou Pulmonary Hospital. In addition, three relevant articles published up to July 2024 were reviewed from both domestic and international databases, including PubMed, China National Knowledge Infrastructure (CNKI), Wanfang Data, Chinese Biomedical Literature Database (CBM), Web of Science, and the Cochrane Library. The clinical features of a total of four pediatric cases of tracheobronchial osteochondroplasia were summarized and analyzed.ResultsA 12-year-old girl with a 5-year history of symptoms was retrospectively reviewed. The patient presented with chronic cough, sputum, hemoptysis, and exertional dyspnea. Comorbidities such as bronchiectasis with cavitation, pneumonia, Klebsiella pneumoniae infection, and sinusitis were observed. Imaging revealed airway wall nodules and structural lung changes. Bronchoscopy showed scattered white nodules; histopathology confirmed mucosal ossification with focal bone marrow formation. Symptomatic improvement was achieved after anti-infective and supportive treatment. A 4-year follow-up revealed recurrent pneumonia and progression of bronchiectasis. Three additional pediatric TO cases (aged 6 months to 9 years) were identified in the literature. Presentations included respiratory symptoms and recurrent infections. Pulmonary function abnormalities, typical radiological and bronchoscopic features, and histopathological evidence were variably reported. Treatments ranged from symptomatic therapy to bronchoscopic intervention. One patient died, one remained stable, and follow-up data were limited.ConclusionTO can develop in children, with atypical chest computed tomography and bronchoscopic changes. Histopathological examination can confirm the diagnosis, and symptomatic treatment is the mainstay.